Immunoreactivity against fibroblast growth factor 8 in alveolar rhabdomyosarcoma patients and its involvement in tumor aggressiveness. (31st December 2022) - Poli, Elena; Barbon, Vanessa; Lucchetta, Silvia; Cattelan, Manuela; Santoro, Luisa; Zin, Angelica; Milano, Giuseppe Maria; Zanetti, Ilaria; Bisogno, Gianni; Bonvini, Paolo
ABSTRACT: Rhabdomyosarcoma (RMS) is an aggressive pediatric soft tissue sarcoma characterized by a very poor prognosis when relapses occur after front-line therapy. Therefore, a major challenge for patients' management remains the identification of markers associated with refractory and progressive disease. In this context, cancer autoantibodies are natural markers of disease onset and progression, useful to unveil novel therapeutic targets. Herein, we matched autoantibody profiling of alveolar RMS (ARMS) patients with genes under regulatory control of PAX3-FOXO1 transcription factor and revealed fibroblast growth factor 8 (FGF8) as a novel ARMS tumor antigen of diagnostic, prognostic, and therapeutic potential. We demonstrated that high levels of FGF8 autoantibodies distinguished ARMS patients from healthy subjects and represented an independent prognostic factor of better event-free survival. FGF8 was overexpressed in ARMS tumors compared to other types of pediatric soft tissue sarcomas, acting as a positive regulator of cell signaling. Indeed, FGF8 was capable of stimulating ARMS cells migration and expression of pro-angiogenic and metastasis-related factors, throughout MAPK signaling activation. Of note, FGF8 was found to increase in recurrent tumors, independently of PAX3-FOXO1 expression dynamics. Risk of recurrence correlated positively with FGF8 expression levels at diagnosis and reduced FGF8 autoantibodies titer, almost as if to suggest a failure of the immune response to control tumor growth in recurring patients. This study provides evidence about the crucial role of FGF8 in ARMS and the protective function of natural autoantibodies, giving new insights into ARMS biology and laying the foundations for the development of new therapeutic strategies.